Simulation Verification of Balancing System Based on Number of Cells - Marek Šimčák; Matúš Danko (Communications - Scientific letters of the University of Zilina, 2021)
This paper deals with the simulation verification of balancing systems with different numbers of batteries. There is a simulation model of the battery with adjustable inputs and a simulation model of flyback converter. These components are interconnected and controlled externally to ensure balancing of individual cells. The batteries are connected in series and a flyback converter is connected to each battery. The outputs of these inverters are connected to the output of all the batteries. So, one can say that this balancing system is designed to lighten the charger. The results of the simulations show the voltage, current and State of Charge (SoC) of the batteries. Simulation models are presented in diagrams. These models were created in the PLECS environment.